Effect of pre-operative educational counseling about routine elements of perioperative care on patient’s experience through their first surgical journey: A randomized control trial - Feba Kurian; Joicy Els Jojo; Santosh Balakrishnan (Asian Journal of Medical Sciences, 2025)
Background: Pre-operative counseling improves patient’s care experience. The trial studied the effect of pre-operative counseling about non-procedural elements of perioperative care, on patients undergoing their life’s first surgery. Aims and Objectives: The aim of our study was to investigate whether educating patients on supporting elements of perioperative care inherent to all surgical procedures, but often unaddressed, have a role in improving patient’s overall surgical experience, especially through their first surgical journey. The objective was to study the effect of a single structured pre-operative educational counselling session about supporting elements of peri-operative care inherent to all surgical procedures in a tertiary care center, on the patient’s personal experience as they journeyed through their first surgical treatment. Materials and Methods: Patients undergoing their first-ever surgery were randomized into test Group A and control Group B. Surgical experience was recorded at 48 h through a regional-language questionnaire. Results: Groups A and B had mean overall surgical experience scores of 71.78 and 62.93, respectively (mean difference (MD) 8.85; P<0.001; the overall surgical experience score was measured using a validated questionnaire). Mean scores in pre-, intraoperative, and post-operative domains were 33.31 versus 30.27 (MD 3.05; P<0.001), 14.47 versus 12.30 (MD 2.15; P<0.001); and 24.00 versus 20.37 (MD 3.63; P<0.001) for the groups, respectively. Significant difference favored the test group in overall surgical experience and specified perioperative periods. Conclusion: Educating patients undergoing their first surgery about elements of perioperative care inherent to hospitalization for any surgery, decreases the anxiety of the patient, and improves patient satisfaction and patients’ care experience in their surgical journey.